ONLINE LEARNING IN HIGHER INSTITUTIONS: EXPLORING CHALLENGES ON STUDENTS’ ENGAGEMENT - Aini Sofia Binti Jasmi; Siti Nurbalqis Binti Mohd Samsudin; Nur Ayza Farhana Binti Abas; Nur Zuhairah Binti Zamzuri; Munirah Binti Mohd Jidi; Nurul Izzah Binti Borhan (International Journal of Accounting, Finance and Business, 2022)
Over the past few years, a new pandemic has just spread to the point that it could kill people suddenly. This outbreak is known as Coronavirus (COVID-19) and now it is becoming endemic to most parts of the world. Many daily activities have been limited in order to maintain the social distance that could spread the virus, including implementing the Movement Constraint Order (MCO). Eventually, we need to adapt to this situation and change our ways of living our lives. One of them is the learning method and learning medium that needs to be transitioned from regular face to face learning to online learning. Learning at the high school and university level, which is normally done physically, has transitioned to online learning and this situation has put the educational system under change, forcing educators and learners to adopt the online teaching methods. This paper aims at reviewing the literature on challenges of online learning. Among problems or challenges faced by the students are difficulties at communicating, stress in having online classes due to lack of resources and technology and few more. The review will give a holistic understanding of the online learning challenges for future researchers and aid to identify the research gap.